Thermally-modulated cell separation columns using a thermoresponsive block copolymer brush as a packing material for the purification of mesenchymal stem cells. (23rd July 2021) - Nagase, Kenichi; Edatsune, Goro; Nagata, Yuki; Matsuda, Junnosuke; Ichikawa, Daiju; Yamada, Sota; Hattori, Yutaka; Kanazawa, Hideko
Abstract : A cell separation column packed with thermoresponsive cationic block copolymer brush-modified beads was developed. The column can separate mesenchymal stem cells by changing the column temperature to alter the polymer brush properties. Abstract : Cell therapy using mesenchymal stem cells (MSCs) is used as effective regenerative treatment. Cell therapy requires effective cell separation without cell modification and cellular activity reduction. In this study, we developed a temperature-modulated mesenchymal stem cell separation column. A temperature-responsive cationic block copolymer, poly( N, N -dimethylaminopropylacrylamide)- b -poly( N -isopropylacrylamide)(PDMAPAAm- b -PNIPAAm) brush with various cationic copolymer compositions, was grafted onto silica beads via two-step atom transfer radical polymerization. Using the packed beads, the elution behavior of the MSCs was observed. At 37 °C, the MSCs were adsorbed onto the column via both hydrophobic and electrostatic interactions with the PNIPAAm and PDMAPAAm segments of the copolymer brush, respectively. By reducing the temperature to 4 °C, the adsorbed MSCs were eluted from the column by reducing the hydrophobic and electrostatic interactions attributed to the hydration and extension of the PNIPAAm segment of the block copolymer brush. From the temperature-modulated adsorption and elution behavior of MSCs, a suitable DMAPAAm composition of the block copolymer brush was determined. Using the column, a mixture of MSC and BM-CD34 + cells was separated by simply changing the column temperature. The column was used to purify the MSCs, with purities of 78.2%, via a temperature change from 37 °C to 4 °C. Additionally, the cellular activity of the MSCs was retained throughout the column separation step. Overall, the obtained results show that the developed column is useful for MSC separation without cell modification and cellular activity reduction.